2020
DOI: 10.1007/s40615-020-00838-z
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Social Determinants of Health and HIV Control in Miami-Dade County ZIP Codes, 2017

Abstract: Background There were 28,055 people living with HIV (PLWH) in Miami-Dade County (MDC) in 2017; 40.1% was either out of care or was not virally suppressed (uncontrolled HIV). The purpose of this study was to determine the association between the social determinants of health (SDOH) and the number of persons with uncontrolled HIV in MDC. Setting This cross-sectional study included PLWH 15 and older with uncontrolled HIV in MDC, 2017. Data on PLWH’s v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…However, although some studies have explored how various demographic factors impact HIV outcomes and treatment adherence among PWH [ 24 , 27 , 28 ], fewer have focused on how SDH factors contribute to the successful control of chronic HIV infection [ 24 , 28 ]. Ecological research previously used principal component analysis to identify communities with lower combined economic stability, education levels, and access to health insurance to have higher rates of uncontrolled HIV [ 24 ]. Our study found similar results in a case-based analysis that modeled each community-level SDH metric on its own.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although some studies have explored how various demographic factors impact HIV outcomes and treatment adherence among PWH [ 24 , 27 , 28 ], fewer have focused on how SDH factors contribute to the successful control of chronic HIV infection [ 24 , 28 ]. Ecological research previously used principal component analysis to identify communities with lower combined economic stability, education levels, and access to health insurance to have higher rates of uncontrolled HIV [ 24 ]. Our study found similar results in a case-based analysis that modeled each community-level SDH metric on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled HIV was defined based on Rojas et al [ 24 ], with slight modification, using participants’ most recent viral load test and CD4 test during the study period ( Supplemental Figure 1 ). A participant was determined to have controlled HIV if their latest viral load test result was undetectable, defined as <200 copies/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers examining the cause behind rising HIV diagnoses and death rates among GBMSM of color, particularly in the deep US southern states, point to the higher-than-average poverty rate and limited opportunities for employment, health care access, and educational achievement [67]. Lastly, people living with HIV (PLWH) appear to be more susceptible to the negative effects of living in high poverty areas as it is associated with lower quality of life [69], unsuppressed viral load and poorer linkage to HIV care [70][71][72], as well as inadequate social support and health service utilization [73,74]. Conversely, employment stability has been shown to improve or maintain HIV care engagement among PLWH [75,76].…”
Section: Economic Stability and Hivmentioning
confidence: 99%
“…23 31 Barriers to sustained undetectable viral load include social determinants of health including racism, homelessness, poverty and access to medical care, which can inhibit one's ability to adhere to a daily medication regimen. [32][33][34][35] Oral HIV pre-exposure prophylaxis (PrEP; 200 mg emtricitabine (FTC) in combination with 300 mg tenofovir disoproxil fumarate (TDF) or 25 mg tenofovir alafenamide (TAF)) has been added to the HIV prevention toolbox within the last decade. When taken daily as an oral medication, PrEP has demonstrated high levels of efficacy (>95%) in preventing HIV transmission among HIV-serodifferent heterosexual couples.…”
Section: Introductionmentioning
confidence: 99%